More than neighbors: a common basis for relationship-centered medicine and science - von Lüpke, Hans (Journal of Nursing, Social Studies and Public Health, 2011)
Causal linearity is still one of the fundaments in scientific thinking. It remains unquestioned in spite of the fact that scientific results in important fields of human life such as genetics and brain function obviously do not follow linearity. Instead, they follow non linear laws as conceptualized in the Chaos Theory, the concepts of complexity or the quantum theory. Because of the fact that the same dynamics can also be found in relational oriented dialogic communication, the traditional gap between natural sciences and humanities seems to vanish. It appears that there has not been made use of the resulting open space for creative interdisciplinary research and practice in human sciences up until now. The reason is obviously a fear of losing stability. The final discussion in this paper deals with the consequences of rigidity and discrepancies in the conceptualization of pathology, rehabilitation and psychotherapy. The balance of the dialectic tension between the pole of security as a human need and the aspect of playful creativity seems to be fundamental for a relationship oriented medicine.
Keywords: biomedicínský výzkum; mezioborová komunikace; Humanities; přírodní vědy; teoretické modely; systémová analýza; Nonlinear Dynamics; Linear Models; Quantum Theory; humanitní vědy; Genetic Research; Systems Analysis; lidé; mozek; lineární modely; Systems Theory; systémová teorie; Brain; systémová integrace; nelineární dynamika; genetický výzkum; Systems Integration; Interdisciplinary Communication; kvantová teorie; Models, Theoretical; Biomedical Research; Natural Science Disciplines; Humans